First observation of the decay Ds+→pn̄ - Athar, S; Patel, R; Yelton, J; Rubin, P; Eisenstein, B; Karliner, I; Mehrabyan, S; Lowrey, N; Selen, M; White, E; Wiss, J; Mitchell, R; et al. (2008)
Using e+e-→Ds*-Ds+ data collected near the peak Ds production energy, Ecm=4170MeV, with the CLEO-c detector, we present the first observation of the decay Ds+→pn̄. We measure a branching fraction B(Ds+→pn̄)=(1.30±0.36-0.16+0.12)×10-3. This is the first observation of a charmed meson decaying into a baryon-antibaryon final state. © 2008 The American Physical Society.